Quality and Value Creation on the Premium Wine Market - Thomas Werdelmann (Journal of Applied Leadership and Management, 2014)
Research questions: How does the value creating process on the wine market work? How is quality perceived and measured? And, are the wineries themselves able to influence the quality perception of their product on the market? Methods: Empirical study across different premium wine producers in Australia and California using a standardized questionnaire.Results: There is a significant interdependency between quality, price, and reputation. Institutions, like wine experts, wineshows, and wine producers influence the quality perception on the market actively and reduce uncertainty and, thereby, create the basis for market transactions.
Keywords: 650